KORELASI KELENGKAPAN FASILITAS BELAJAR TERHADAP HASIL BELAJAR PKN DI SMA 2 POLEWALI - Suhaebah Nur (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2015)
Educational research in this thesis aims to obtain objective information about the state of completeness of learning facilities at SMAN 2 Polewali and to determine whether there is a correlation completeness learning facility to the learning outcomes in SMA 2 Polewali. This research is a quantitative research using descriptive analysis. The study population was all students in SMA 2 Polewali class X, XI, and XII SMA totaling 91 people. While the samples are all students at SMA 2 Polewali by using the system pegambilan sample of census system. Collecting data in this study conducted by (1) Questionnaire, (2) observation, (3) Interview. The data were analyzed descriptively. Then after that the results of a questionnaire about the completeness facilities Civics learning and learning outcomes of students, and then to determine the correlation learning outcomes completeness to facilities of students at SMA 2 Polewali, the data were analyzed using product moment correlation coefficient. This is to determine the level of correlation between the two variables. From the calculation of correlation figures of 53.10, then the alternative hypothesis (Ha) is accepted and nil hypothesis (Ho) is rejected. Means there is a correlation / significant influence between the variables X and Y. Therefore, this suggests that there is a relationship / high impact among the variables of learning facilities with variable outcomes study in SMA 2 Polewali.